Effect of Abutment Type and Tightening Sequence on Torque Maintenance Capacity after Mechanical Cycling in Splinted Implant-Supported Restorations - Leonardo Jiro Nomura Nakano; Laís Carolina Landim Gomes; Talita Suelen de Queiroz; Tarcisio José de Arruda Paes-Junior (MDPI AG, 2021)
The aim of this study was to compare the screw removal torque of mini-conical prosthetic components and straight trunnion of indexed morse taper implants after mechanical cycling. The sample consisted of 40 implants and 20 mini-conical prosthetic components (MC group) and 20 straight trunnion components (ST group). Each group consisted of 10 specimens, with 2 implants in each, and cobalt-chromium metallic crowns were screwed into each sample. The components of the MC group received a torque of 20 N-cm with a digital torque wrench, and after 10 min were retightened with the same value as the initial torque. The components of the ST group received a torque of 30 N-cm, with a digital torque wrench, and after 10 min, they were retightened with the same value. The screws of the respective crowns of the two groups received a torque of 10 N-cm and after 10 min were retightened with the same value. Each group was subjected to the fatigue test in a mechanical cycler at 2,000,000 cycles, with a load of 250 N and frequency of 4 Hz. At the end of the fatigue test, the loosening torque of each screw of the specimens was measured through a digital torque wrench. The data were analyzed by two-way ANOVA and a Tukey test. In both groups, there were loss of torque. The results showed no statistic difference between MC and ST groups (p > 0.05).